PENGENDALIAN KUALITAS AMPLANG MENGGUNAKAN SEVEN TOOLS DI UD. KELOMPOK MELATI - Nina Hairiyah; Raden Rizki Amalia; Nuryati Nuryati (AGROINTEK, 2020)
UD Kelompok Melati is a home industry the processed of amplang.On the process, there is a deficiency product affect to not optimal profit for the industry. The aims of this research is find of the damage kind cause of amplang damage and step to minimize of amplang damage it used with old seven tools (flow chart, Check Sheet, Histogram, Control Chart and Cause and Effect Diagram). Data collection techniques are observation, interview and literature study. The research showed that the deficiency contained at UD Kelompok Melati is amplang cannot expand and perforated. The according of result by check sheet obtained percentage of defects that is 62,9%. The histogram shows from 1000 amplang to the samples, it has 389 amplang that is not expending and 240 amplang had a hole. Seen from control chart it shows the deformities are normal because it is not to cross either the top or down of the line, but quality control has to be optimum because the data of demage from check sheet is over 50%. The factor of damage according by cause and effect diagram is raw material, man and method.